2016
DOI: 10.1002/cyto.a.22853
|View full text |Cite
|
Sign up to set email alerts
|

Labeling nanoparticles: Dye leakage and altered cellular uptake

Abstract: In vitro and in vivo behavior of nanoparticles (NPs) is often studied by tracing the NPs with fluorescent dyes. This requires stable incorporation of dyes within the NPs, as dye leakage may give a wrong interpretation of NP biodistribution, cellular uptake and intracellular distribution. Furthermore, NP labeling with trace amounts of dye should not alter NP properties such as interactions with cells or tissues.To allow for versatile NP studies with a variety of fluorescence-based assays, labeling of NPs with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
94
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 92 publications
(97 citation statements)
references
References 47 publications
1
94
0
Order By: Relevance
“…15 We should note that the encapsulation of dyes into NPs can cause misinterpretation of their 16 cellular uptake in flow cytometry due to potential dye leakage [45][46][47]. We therefore confirmed 17 that no dye leakage has taken place by incubating RBE4 cells with PACA NPs at 4 ºC [48]. In 18 addition, CLSM images confirmed that the NPs were internalized.…”
mentioning
confidence: 54%
“…15 We should note that the encapsulation of dyes into NPs can cause misinterpretation of their 16 cellular uptake in flow cytometry due to potential dye leakage [45][46][47]. We therefore confirmed 17 that no dye leakage has taken place by incubating RBE4 cells with PACA NPs at 4 ºC [48]. In 18 addition, CLSM images confirmed that the NPs were internalized.…”
mentioning
confidence: 54%
“…In order to investigate the nanoparticles' uptake mechanisms, HEK293 cells were prepared in 6-well plates as described above and pretreated with the inhibitors (1.25 mM AMD, 45 lM CPZ, 15 lg/ml IND, and 3 lg/ml AZD) for 60 min at 37 C. For determining dye leakage or contact mediated dye transfer, uptake studies were repeated at þ4 C for PLGA 230 or PLGA 160 (Ray et al 2016, Snipstad et al 2016. Then the nanoparticles (1.25 Â 10 10 particles/ml) were added and cellular uptake was evaluated by flow cytometry following 3 h and 24 h of incubation for PLGA 230 or PLGA 160 nanoparticles, respectively.…”
Section: Independent Variables Low Highmentioning
confidence: 99%
“…As release of drugs is very difficult to monitor in complex biological media and in live cells, fluorescent dyes are used as model cargos for polymer NPs. [17][18][19][20][21][22][23] Dye-loaded polymeric NPs are attractive systems to address the problem of cargo leakage. On one hand, they are powerful tools for fluorescence bioimaging in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…The encapsulated fluorescent dyes are excellent probes that can report on the cargo release from nanocarriers. [17][18][19][20][21][22][23] Dye-loaded and drug-loaded NPs share two key common requirements. The first requirement is the high loading of cargo.…”
Section: Introductionmentioning
confidence: 99%